Refinamento psicométrico da escala de atitudes para o perdão (EFI) - Andrade, Thiago Francisco de (2014)
This thesis aimed to test the psychometric properties of the brazilian version of Enright Forgiveness Inventory (EFI) and propose, based on the estimated parameters, a reduced version of the instrument. EFI is a self-administered instrument that was developed to operationalize the theoretical model of attitudes toward forgiveness, proposed by Robert Enright and his colleagues. This model postulates the existence of six attitudinal components for forgiveness: positive affects, negative affects, positive judgments, negative judgments, positive behaviors, and negative behaviors. The EFI consists of 60 items answered on a six-point Likert-type scale (ranging from "Strongly disagree" to "Strongly agree") that seek to represent the six components of the theoretical model. The instrument also has a single-item scale called "Forgiveness item", which serves as an indicator of external validity. Data from 1,372 participants of both sexes, aged between 13 and 83 years and for the most part, students were gathered. These data were analyzed separately in two studies, both conducted by statistical packages in R: in Study 1, Confirmatory Factor Analyses were conducted with the objective of analyzing the plausibility of the theoretical model of six components. The results suggest that the proposed model shows good fit indices (CFI = .92, RMSEA = .046), especially when compared to alternative models (univariate and hexafactorial with additional second-order factors). In Study 2, item analyzes were performed by means of Item Response Theory. The results indicated that all items have good psychometric qualities, as measured by discrimination and information (precision) coefficients. It was also evaluated the adequacy of response categories. In this step were selected from among each subscale, the five items with the best parameters, reducing the total scale length in half. Results of a new CFA indicate the adequacy of the reduced compared to the original version with 60 items. Despite these results, further research is recommended to examine the properties of this reduced version in different samples used in this study.